2007
DOI: 10.1249/01.mss.0b013e31804ec08d
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Function of the Vastus Medialis with Clinical Implications

Abstract: VMO activity was pronounced during the weight-bearing conditions, with increased medial and lateral knee movements. This suggests that the VM should not be considered simply as a knee extensor or as a muscle whose main role is to maintain normal patellar tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…Each exercise was repeated three times and exercises were separated by a 30 s rest period (Toumi et al, 2007). The performance order of the tests was determined using a random number table for all volunteers.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Each exercise was repeated three times and exercises were separated by a 30 s rest period (Toumi et al, 2007). The performance order of the tests was determined using a random number table for all volunteers.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…After careful preparation of the skin (Toumi et al, 2006(Toumi et al, , 2007 the electrode pairs were placed over the muscle belly of the respective muscles (Toumi et al, 2006(Toumi et al, , 2007. A reference electrode was placed over the patella.…”
Section: Emg Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that in 45% of their pathological cohort one nerve branch was identified, whereas two branches were identified in 55% of their cohort. On further analysis, these differences in innervation were significantly correlated with the degree of Javadpour et al (1991) 15/15 1 in 100 Jojima et al (2004) 10/10 1 in 100 Lefebvre et al (2006) 17/39 1 in 44 22/39 2 in 56 Lieb and Perry (1968) 5/6 1 in 83 1/6 2 in 17 Nozic et al (1997) 50/50 2 in 100 Ono et al (2005) 2/2 2 in 100 Özer et al (2004) 20/20 2 in 100 Peeler et al (2005) 32/32 1 in 100 Thiranagama (1990) 30/30 2 in 100 Toumi et al (2007) 10/10 2 in 100 Weinstabl et al (1989) 115/115 1 in 100 a Studies assessing pathological knees. patellofemoral cartilaginous damage.…”
Section: Innervationmentioning
confidence: 99%
“…Outro fator associado é o posicionamento anatômico deste músculo, ou seja, o VM também apresenta uma pequena região de continuidade direta inserida no tendão patelar e não está somente inserido na borda medial da patela (Toumi et al, 2007). O papel do VL na estabilização da patela apresenta relevância pelo fato de estar localizado no septo lateral intermuscular unido à linha áspera do fêmur, consequentemente, fixado na borda supralateral da patela (Bevilaqua-Grossi, Monteiro-Pedro, Souza, Silva, & Bérzin, 2004).…”
Section: Atividade Electrica Do Vasto Lateral E Medial Com O Exercíciunclassified